1958
DOI: 10.1113/jphysiol.1958.sp006042
|View full text |Cite
|
Sign up to set email alerts
|

The release of chemical transmitter from the sympathetic nerves of the intestine of the cat

Abstract: In a previous paper (Brown & Gillespie, 1957) we have shown that the noradrenaline released when the sympathetic nerve supply to the spleen is stimulated can be estimated in the venous blood leaving the organ. The maximum output per stimulus occurred at frequencies of 30/sec. Administration to the animal of substances blocking the effect of the liberated transmitter on the innervated cells increased the output of noradrenaline at frequencies below 30/sec.These experiments were made on the spleen of the cat bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

1961
1961
1989
1989

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(16 citation statements)
references
References 5 publications
1
15
0
Order By: Relevance
“…Most previous experiments in which norepinephrine overflow in response to nerve stimulation has been studied were carried out using stimulation frequencies ranging from 10 to 50 Hz or more (16)(17)(18)(19)(20)(21)(22)(23). In these experiments carried out on isolated, perfused organs, the amount of norepinephrine released into the venous effluent or perfusate was determined mainly by bioassay techniques (16)(17)(18)(19), spectrofluorometric measurements (22), or through the use of labeled norepinephrine (20,21,23).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Most previous experiments in which norepinephrine overflow in response to nerve stimulation has been studied were carried out using stimulation frequencies ranging from 10 to 50 Hz or more (16)(17)(18)(19)(20)(21)(22)(23). In these experiments carried out on isolated, perfused organs, the amount of norepinephrine released into the venous effluent or perfusate was determined mainly by bioassay techniques (16)(17)(18)(19), spectrofluorometric measurements (22), or through the use of labeled norepinephrine (20,21,23).…”
Section: Figurementioning
confidence: 99%
“…In these experiments carried out on isolated, perfused organs, the amount of norepinephrine released into the venous effluent or perfusate was determined mainly by bioassay techniques (16)(17)(18)(19), spectrofluorometric measurements (22), or through the use of labeled norepinephrine (20,21,23). Mainly because previous techniques have lacked the sensitivity needed to detect small changes in the levels of endogenous catecholamines in the plasma, it has been impossible to accurately measure the effects of low-frequency stimulation on the order of 1-3 Hz and correlate them with physiological responses under basal conditions so far in vivo.…”
Section: Figurementioning
confidence: 99%
“…In a series of papers (Brown & Gillespie, 1957;Brown, Davies & Gillespie, 1958;Brown, Davies & Ferry, 1961;Blakeley, Brown & Ferry, 1963) experiments have been described in which the postganglionic sympathetic fibres have been stimulated to an organ (mostly the spleen) in the cat and the amount of noradrenaline has been measured in the blood in the vein leaving the organ. The effect of antiadrenaline substances, in particular phenoxybenzamine and Hydergine (which may be described as dihydroergotoxine methanesulphonate), was determined, and it was observed that in their presence the output of noradrenaline was greatly increased when stimulation was applied at 10 shocks/ sec, though at a higher frequency the increase in the output was much less.…”
mentioning
confidence: 99%
“…These results suggest a direct release of pressor amines from the adrenal medulla while nervous influence is reduced by the ganglion blocker. Brown & Gillespie (1957) and Brown, Davies & Gillespie (1958) have shown that administration of phenoxybenzamine causes a greater release of amine from a tissue when the sympathetic nerve supply is stimulated than takes place without the influence of this 2-halogenoethylamine, while Schapiro (1958) demonstrated an increased urinary excretion of noradrenaline and a loss of catechol amines from the heart, adrenals and spleen after giving this compound.…”
Section: Discussionmentioning
confidence: 99%